2001
DOI: 10.3346/jkms.2001.16.s.s66
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Chemoprevention by Ginseng in Mouse Liver and Other Organs

Abstract: Oral administration of red ginseng extracts (1% in diet for 40 weeks) resulted in the significant suppression of spontaneous liver tumor formation in C3H/He male mice. Average number of tumors per mouse in control group was 1.06, while that in red ginseng extracts-treated group was 0.33 (p<0.05). Incidence of liver tumor development was also lower in red ginseng extracts-treated group, although the difference from control group was not statistically significant. Anti-carcinogenic activity of white ginseng extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 1 publication
1
16
0
Order By: Relevance
“…They concluded that Rg3 + Rg5 had anticarcinogenic effects. Similar to the current observations, Nishino et al [70] reported that oral administration of red ginseng extracts significantly suppressed spontaneous liver tumour formation in C3H/He male mice.…”
Section: Discussionsupporting
confidence: 77%
“…They concluded that Rg3 + Rg5 had anticarcinogenic effects. Similar to the current observations, Nishino et al [70] reported that oral administration of red ginseng extracts significantly suppressed spontaneous liver tumour formation in C3H/He male mice.…”
Section: Discussionsupporting
confidence: 77%
“…The injection of rats with ginseng only, led to a significant increase in DNA content in kidney cells. These effects may be due to the antioxidant nature of ginseng [33].…”
Section: Discussionmentioning
confidence: 99%
“…Nishino et al [33] reported that ginseng can increase body resistance to many harmful factors and protect tissue from damage and could inhibit lipid peroxidation of rat liver and kidney. Lee et al [34] stated that ginseng may reduce cell damage induced by toxic substance and acts to stabilize cell membranes there by providing protection against toxic agents induced tissue injury.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, oral administration of a white ginseng-containing Chinese medicinal prescription known as ren-shen-yang rong-tang, resulted in the suppression of skin tumor promotion by 12-otetradecanoylphorbol-13 acetate in 7, 12-dimethylbenz[a] anthraceneinitiated CD-1 mice, suggesting the usefulness of ginseng in the field of cancer prevention 46 . Isoliquiritigenin is a natural flavonoid isolated from licorice, shallot and bean sprouts that has significantly inhibited, in a doseand time dependent manner, the proliferation of cancer cells in the A549 human lung cancer cell line.…”
Section: Andrographis Paniculatamentioning
confidence: 99%